Thinking outside the block: External focus of attention shortens reaction times in collegiate track sprinters - Miles, Garrett (My University, 2018)
Reaction time during a sprint start can have a dramatic effect on the outcome of a short- distance running race. While, focusing attention on an external cue has been shown to enhance skill acquisition and performance (Wulf, 2013), track and field coaches tend to provide instructions to their athletes that promote an internal focus of attention (Porter et al., 2010). Therefore, the purpose of this study was to determine whether instructions promoting external versus internal focus of attention would influence reaction time (RT) during a track sprint start task. Additionally, a primary interest was to determine if focus of attention manipulation will influence primarily central processes during movement preparation, or peripheral processes during movement execution. Twelve Division III collegiate track sprinters (ages 18-23) completed three separate testing sessions at least 2 days apart. Reaction times were assessed under three different conditions: i) external focus (EF) where subjects focused on pushing the blocks away; ii) internal focus (IF) where subjects focused on extending the knees; and, iii) no focus instruction (NF). Muscle activity was recorded from the left and right vastus lateralis and left and right medial gastrocnemius muscles. Rear foot RT during the EF condition (Mean=212.11 ms, SE=8.45 ms) was significantly shorter than both IF (Mean=234.21, SE=5.76 ms) and NF conditions (Mean=236.87, SE=8.82). Front foot RT was also significantly shorter during EF (Mean=250.24, SE=17.24 ms), compared to IF (Mean=266.98, SE=16.44 ms) but not shorter than NF (Mean=268.73, SE=14.23 ms). Muscle activity also indicated a shorter premotor RT under the EF condition (Mean=157.75, SE=7.38 ms), compared to IF (Mean=181.90, SE=5.72) and NF (Mean=173.60, SE=7.30 ms). Our findings indicate that adopting an EF improves RT during sprint starts. This improvement likely originates from a reduction in movement preparation time. These findings have the potential to contribute to the development of new coaching techniques when the aim is to improve the reaction time of athletes.
Keywords: Sprinting -- Training; Exercise -- Physiological aspects -- Testing